Teori Agenda Setting dan Citra Pemerintah: Analisis Pemberitaan Korupsi dan Penurunan Citra Pemerintahan SBY - Mr Ansor (Program Studi Ilmu Komunikasi, 2011)
Media play an important role in political life. In agenda setting theory, what is considered important by the media will be important as well for the audience (public). This includes how the media show the reality will influence the way public perceive it. In the corruption issue context in Indonesia, this research found that corruption is considered as an important agenda in the media. It can be seen through the placement of news in the headlines, column length, and paragraphs. Then, most of it was also delivered in an unfavorable way which influences public's perception. Thus, the image of the government continues to decline, especially in law enforcement and the handling of corruption cases.